PEMBENTUKAN KARAKTER RELIGIUS DAN AKHLAKUL KARIMAH MELALUI GERAKAN LITERASI AL-QUR’AN DI MADRASAH DINIYAH DESA PANDAN GALIS PAMEKASAN - Nasir, Moh.; Prayoga, Iwan (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2024)
This community service was motivated by the weak religious character and moral values of students at the Madrasah Diniyah in Pandan Village, Galis District, Pamekasan Regency. This condition was evident in their lack of discipline in worship, low interest in reading the Qur'an, and minimal appreciation of noble moral values in their daily lives. Therefore, a systematic effort is needed through a Qur'an literacy movement as a means of internalizing Islamic religious and moral values. The method of implementing this community service uses a participatory-educational approach, with the following stages: (1) socialization of the program to the caregivers and teachers of Madrasah Diniyah; (2) training students in the habit of reading and contemplating the Qur'an; (3) regular assistance in Qur'an literacy activities; and (4) evaluation of the results of guidance through observation of students' religious attitudes and morals. The activities were carried out collaboratively between the community service team, Madrasah Diniyah teachers, and local religious leaders. The results of the community service showed a significant increase in the religious attitudes and good character of the students. Students became more disciplined in reading the Qur'an, showed polite behavior towards teachers and friends, and were more active in religious activities. The Qur'an literacy movement proved to be effective as a medium for shaping religious and Islamic moral character, while strengthening the Qur'anic culture in the madrasah environment and the community of Pandan Village.